The Predictive Value of the G8 Questionnaire in Older Patients with Lung Cancer or Mesothelioma before Systemic Treatment. Issue 2 (February 2023) - Wu, X.; Kumar, R.; Milner-Watts, C.; Walder, D.; Battisti, N.M.L.; Minchom, A.; Bhosle, J.; O'Brien, M.E.R.
Abstract: Aims: The standard evaluation of older lung cancer or mesothelioma patients for systemic anti-cancer treatment, based on performance status, is inaccurate. We used the G8 questionnaire to assess a patient's fitness for chemotherapy and explored the correlations between G8 scores, treatment decisions and clinical outcomes. Materials and methods: In total, 201 older patients (≥70 years) with advanced lung cancer or mesothelioma were prospectively assessed by standard clinical methods and a G8 questionnaire. Treatment decisions before and after reviewing the G8 score were documented. Patients were divided into low (<11), intermediate (11–14) and high (>14) G8 score groups. Patients' characteristics, treatment plans and clinical outcomes among each G8 score group were compared. Similar analyses were compared between good (<2) and poor (≥2) performance status. Results: 10.1% of patients' treatment plans changed after oncologists reviewed G8 scores. The G8 score correlated inversely with performance status. More patients with low G8 scores (22.5%) were offered the best supportive care compared with 4.5% in intermediate and 1.9% in high G8 score groups. More patients (30.1%) with low G8 scores had treatment changed from chemotherapy to best supportive care on the planned day of their treatment, compared with intermediate (7.5%) and high (6.1%) G8 score groups. High G8 score patients received higher chemotherapy intensity and survived longer than patients with intermediate or low G8 scores. Conclusions: The G8 score with two cut-off values can predict functional status, chemotherapy tolerability and prognosis in older patients with lung cancer or mesothelioma, thus supporting oncologists on treatment decisions for this population. Highlights: The G8 scores correlate inversely with performance status. Low G8 scores can predict a rapid functional decline of older patients with lung cancer or mesothelioma. The G8 score with two cut-off values can predict chemotherapy tolerability and prognosis. Our findings reinforce the clinical utility of the G8 scores to support oncologists on treatment decisions and chemotherapy intensity.